PENGEMBANGAN MEDIA PEMBELAJARAN GAMES COUNTDOWN CALLENGE BERBANTUAN WORDWALL PADA MATA PELAJARAN IPAS KELAS III SD - Widiartini, Luh; I Made Sedana; I Komang Wahyu Wiguna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning media with an attractive and interactive design has the potential to encourage increased student engagement in the learning process. However, in reality, the need for engaging and interactive media is still not fully met, resulting in low student participation and easily boredom during learning. This research aimed to develop learning media that can support the effectiveness of the teaching and learning process. The media developed was the Countdown Callenge game supported by a Wordwall for the topic